Enhancement of Aeroengine Combustion Chamber Air Cooling Holes Design for Emission Reduction and Pattern Factor Control - Masoud Hajivand (Journal of Mechanical Engineering)
The results of a comprehensive numerical analysis of temperature uniformity and NOx and CO emission predictions in an aeroengine annular combustor liner, conducted by geometrical modifications through design changes in primary cooling air, including effusion cooling holes, are shown in the paper. A total of five geometric configurations were studied using computational fluid dynamics (CFD) simulations in ANSYS CFX. The adopted combustion model was sort of a combination of the finite-rate (i.e., chemistry, chemical processes) and eddy dissipation model (FRC/EDM). Further, the combustion of liquid kerosene (C10H22) with air, subsequent to the evaporation of fuel droplets, was simulated, and the Rosin-Rammler droplet size distribution was used in spray modeling for accurate depiction of fuel atomization. Both thermal and prompt formation mechanisms of NOx were considered, while k-ε model for turbulence was adapted to capture the nature of emission. An annular combustion chamber of realistic dimensions with a double radial air swirler was modelled in 3D CAD to undertake this study for good, tangible results. Built contour plots allowed to analyze the temperature distribution and NOx concentration along the axis from the center of the injector. Charts on the pattern factor, temperature, and NOx and CO concentrations at the outlet of the combustor served as performance metrics. The simulation was implemented with a two-step chemical kinetics scheme for kerosene combustion with the P1 radiation model, which would give an accurate thermal radiation prediction. One of the major objectives of this research is to compare the CFD results at the combustor outlet with gas dynamic and thermodynamic calculations that have been carried out using AxStream software at the Department of Aeroengine Design, Kharkiv Aviation Institute. It is important to emphasize that the mean deviation of gas dynamic results obtained from AxStream and CFD simulation results was found to be insignificant, hence the CFD approach has been validated. The results testify that redesigning the combustor liner, especially in the design related to primary and effusion cooling holes, drastically reduced NOx and CO emissions. Also, these design modifications have helped in reducing or improving temperature uniformity at the combustor outlet, either way enhancing combustion efficiency and performance.